Experimental study on mechanical property and pore structure of concrete for shotcrete use in a hot-dry environment of high geothermal tunnels. (10th June 2018) - Cui, Shengai; Liu, Pin; Cui, Enqi; Su, Jiao; Huang, Bo
Highlights: The hot-dry environment was simulated in a laboratory. The effects of adding fiber materials on mechanical property and pore structure were investigated. The mathematical model of strength and pore structure was established. Abstract: In order to examine the deterioration mechanism and improvement measures in 100 °C hot-dry environments of high geothermal tunnels, the mechanical experiments and pore structure determinations were performed to study the macroscopic mechanical properties and pore structure characteristics of concrete for shotcrete use. The results show that: (1) in the hot-dry environments, the compressive strength and splitting tensile strength of basic mix proportion condition (BP) both decrease sharply after 7 days. By adding steel fibers or basalt fibers into concrete mix, the two kinds of strength of concrete are obviously improved, and the effect of steel fiber is significantly better than that of basalt fiber. Moreover, the improving effect of waved steel fiber among three kinds of fibers on compressive strength is the best. Compared with that of BP, the compressive strength of waved steel fiber condition (SF-W) increases by 17.2%, 37.5%, and 119.4% at 1-day, 7-day, and 28-day age respectively. The improving effect of hooked end steel fiber among three kinds of fibers on splitting tensile strength is the best. Compared with that of BP, the splitting tensile strength of hooked end steel fiber condition (SF-HE) increases by 88.5%, 72.6%, and 110.6% at 1-day, 7-day, and 28-day age respectively. (2) The median pore diameter and average pore diameter of BP at each age are higher than those of mixed fiber conditions at corresponding age. With the increase of age, the total porosity and the porosity of harmful pore (pore diameter >100 nm) of BP condition in the hot-dry environments increase rapidly. The addition of fiber materials effectively reduces the total porosity and the porosity of harmful pore, and the optimization effect of steel fiber on pore structure is better than that of basalt fiber. Compared with BP, the total porosities of SF-HE and SF-W decrease by 54.6% and 60.1%, and the porosities of harmful pore of SF-HE and SF-W decrease by 73.7% and 77.5% respectively. (3) The compressive strength and splitting tensile strength of double mix of steel fibers and silica fume condition (SF-HE + Si) are obviously lower than those of SF-HE, and the total porosity and the porosity of harmful pore are obviously higher than that of SF-HE in the hot-dry environments. (4) Compared with Menger sponge model, the fractal dimension based on thermodynamic method can describe the pore size distribution in the whole test range more comprehensively, and it is more suitable for solving the fractal dimension of concrete in this kind of environments. (5) The multi-factor strength mathematical model considering the influence of fractal dimension and composite porosity is in good agreement with the experimental results, thus, it can accurately be used to describe the quantitative relationship between strength and pore structure parameters.